A new ant-associated species of Laelaspis (Acari: Mesostigmata: Laelapidae) from Iran - Arsalan Khalili-Moghadam; Alireza Saboori; Alireza Nemati; Azadeh Zahedi Golpayegani (Persian Journal of Acarology)
In this paper, a new species of the genus Laelaspis Berlese, L. angustiseta sp. nov. is described based on morphological characters of the adult female specimens collected in association with Tapinoma erraticum (Latreille) and Tapinoma simrothi Krausse (Hymenoptera: Formicidae) in Chaharmahal va Bakhtiari Province, Iran.